2006
DOI: 10.2140/agt.2006.6.71
|View full text |Cite
|
Sign up to set email alerts
|

Generalised Swan modules and the D(2) problem

Abstract: We give a detailed proof that, for any natural number n, each algebraic two complex over C_n \times C_\infty is realised up to congruence by a geometric complex arising from a presentation for the group.Comment: This is the version published by Algebraic & Geometric Topology on 24 February 200

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The work of W. J. Browning [3] can be applied in these cases and this has led to proofs of the D2 property for finite abelian groups [3], [5], [11], dihedral groups [25], the polyhedral groups T , O, I [15] (exhausting the finite subgroups of SO(3)) and various metacyclic groups [21], [33], [46]. It has also been shown for various infinite abelian groups [12], [13] and free groups [20].…”
Section: Introductionmentioning
confidence: 99%
“…The work of W. J. Browning [3] can be applied in these cases and this has led to proofs of the D2 property for finite abelian groups [3], [5], [11], dihedral groups [25], the polyhedral groups T , O, I [15] (exhausting the finite subgroups of SO(3)) and various metacyclic groups [21], [33], [46]. It has also been shown for various infinite abelian groups [12], [13] and free groups [20].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the D(2) property in known to hold only in comparatively few cases. These include cyclic groups, products of the form C 1 C n (Edwards [2]) and, more relevantly to the present paper, the dihedral groups D 4nC2 (Johnson [5; 6]).…”
Section: Introductionmentioning
confidence: 99%
“…The first finite non-Abelian non-periodic group shown to have the D (2) property was the dihedral group of order 8 (Mannan [10]). The methodology adopted in [10] was an instance of the approach developed and laid out in [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For connected X with certain fundamental groups, it has shown been shown that X must be homotopy equivalent to a finite 2-complex (see for example Johnson [7], Edwards [4] and Mannan [9]). However no general method has been forthcoming.…”
Section: Introductionmentioning
confidence: 99%